2013
DOI: 10.4102/sajbm.v44i3.162
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of box office performance in the film industry revisited

Abstract: The film industry is a significant player in the global economy. It calls for significant up-front investments with the result that analysts, studios and investors alike are interested in predicting box office success as part of financial risk management.This study utilises global box office revenue in assessing the effects of eight explanatory variables, identified from previous studies, in the explanation of revenue. Nearly three decades after the seminal study the extension of the original methodology to gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
4
18
0
5
Order By: Relevance
“…With regard to movie awards, we could consider that they are a factor external to the movie that give it an extra extrinsic characteristic; however, as we have seen in the theoretical review, the awards are the product of the ratings by critics, scholars and the public (Deuchert et al, 2005;Terry et al, 2005;Pangarker & Smit, 2013). These comments come from people who have seen the movie, and therefore they take on an experiential value and function as such with regard to moviegoers (Henning-Thurau, Wiertz & Feldhaus, 2012).…”
Section: Movie Theaters Could Increase Their Profits If They Enacted mentioning
confidence: 99%
“…With regard to movie awards, we could consider that they are a factor external to the movie that give it an extra extrinsic characteristic; however, as we have seen in the theoretical review, the awards are the product of the ratings by critics, scholars and the public (Deuchert et al, 2005;Terry et al, 2005;Pangarker & Smit, 2013). These comments come from people who have seen the movie, and therefore they take on an experiential value and function as such with regard to moviegoers (Henning-Thurau, Wiertz & Feldhaus, 2012).…”
Section: Movie Theaters Could Increase Their Profits If They Enacted mentioning
confidence: 99%
“…Обычно конкретные условия контракта между дистрибьютором и кинотеатрами конфиденциальны, а дележу подлежит доход бокс-офиса (кассовые сборы). Со стороны кинотеатров недобросовестное поведение может выражаться в искажении истинного размера боксофиса [Hanssen, 2000;Caves, 2001;Eliashberg, Elberse, Leenders, 2005;Pangarker, Smit, 2013].…”
Section: дистрибьюцияunclassified
“…However, their study failed to explain the exact mechanism and conflicted with Feng and Sharma (2016) study, which showed, with quantile regressions, that high-budget films were not always successful in the Chinese movie market. Others have postulated that action movies and sequel movies are more likely to be high grossing, as evidenced by the fact that more than half of the highest-grossing movies belong to these genres, including Toy Story, The Dark Knight, Harry Potter and Transformers (Pangarker and Smit 2013). However, as mentioned before, these highest-grossing movies only account for the tip of the iceberg and hardly represent the long tail of the less-famous movies unknown to the public.…”
Section: Introductionmentioning
confidence: 95%